Every time we say goodbye : a novel [large type] - Jenner, Natalie (Center Point Large Print, 2024)
"In 1955, Vivien Lowry is facing the greatest challenge of her life. Her latest play, the only female-authored play on the London stage that season, has opened in the West End to rapturous applause from the audience. The reviewers, however, are not as impressed as the playgoers and their savage notices not only shut down the play but ruin Lowry's last chance for a dramatic career. With her future in London not looking bright, at the suggestion of her friend, Peggy Guggenheim, Vivien takes a job as a script doctor on a major film shooting in Rome's Cinecittà Studios. There she finds a vibrant movie-making scene filled with rising stars, acclaimed directors, and famous actors in a country that is torn between its past and its potentially bright future, between the liberation of the post-war cinema and the restrictions of the Catholic Church that permeates the very soul of Italy. As Vivien tries to forge a new future for herself, she also must face the long-buried truth of the recent World War and the mystery of what really happened to her deceased fiancé."--